2018
DOI: 10.15544/mts.2018.43
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenon of Abandoned Villages and Its Impact on Transformation of Rural Landscapes

Abstract: The problem examined in this research is how the loss of rural settlements, small towns, villages and farms contributes to changes in rural landscape and how can this change be managed? The survey was conducted in matching locations in Poland, Slovakia, Germany and in the southern part of Cyprus. The research methods were based on the analysis of source materials and on field analyses in the studied regions. Source research included searching for information in a literature on the subject, as well as planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…The last column of the table in Appendix C reports this classification. Although this typology is heavily used and respected (Andráško and Ira, 2010 ; Huba et al 2010 ; Bleha, 2011 ; Jaszczak et al 2018 ; Klobučník et al 2018 ), it produces classifications that are not very compliant with the present viability assessment of municipalities. The optimal scaling procedure of Young ( 1981 ) employed to transform the ordinal scale of the categories introduced by Gajdoš et al ( 2009 ) into continuous measurements identified that the correlation may vary between 0.229 and −0.783.…”
Section: Resultsmentioning
confidence: 99%
“…The last column of the table in Appendix C reports this classification. Although this typology is heavily used and respected (Andráško and Ira, 2010 ; Huba et al 2010 ; Bleha, 2011 ; Jaszczak et al 2018 ; Klobučník et al 2018 ), it produces classifications that are not very compliant with the present viability assessment of municipalities. The optimal scaling procedure of Young ( 1981 ) employed to transform the ordinal scale of the categories introduced by Gajdoš et al ( 2009 ) into continuous measurements identified that the correlation may vary between 0.229 and −0.783.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, a significant part of the depopulated villages be-gin to function primarily as tourist attractive areas and a large share of the new houses serve recreational purposes as second homes, guesthouses or homes for rent, which is a typical trend in many regions with attractive landscapes. The recreational and tourism functions are very often proposed as the most common strategies for revival of the abandoned villages in various countries (Filipe & Mascarenhas 2011;Di Figlia 2016;Jaszczak et al 2018). Unfortunately, many of the new buildings in the study area do not follow the traditional style of the regional architecture and they are not well integrated into the landscape which disturb the spatial order of the cultural landscape and landscape character.…”
Section: Discussionmentioning
confidence: 99%
“…Plieninger et al 2016;Lasanta et al 2017). The phenomenon of deserted villages (and towns) is the most extreme result of the depopulation and land abandonment and it has also gained importance in the recent research (Filipe & Mascarenhas 2011;Mares et al 2013;Hons 2014;Latocha 2015;Di Figlia 2016;Wolski 2016;Jaszczak et al 2018;Güler & Kâhya 2019). The causes of depopulation are both global, linked to the universal trends like globalization, urbanization, global market, industrialization, EU policies and subsidies etc., but they are also highly related to the sitespecific constraints, especially to the local environmental factors (Súľovský et al 2017;Telbisz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Figlia [21] hopes that although the abandoned villages ceased to exist, their memory could be preserved. Rural landscape changes due to abandoned settlements are generally emphasized [22].…”
Section: Introductionmentioning
confidence: 99%